Effective Protection, Transportation Costs, and the Location of Firms - John M. Hartwick (Queen's University, Department of Economics, 1970)
A group of well-known models in location theory can be classified according to three salient properties–the presence or absence of homogeneity in the geographic space with respect to first the distribution of consumers, secondly the distribution of inputs for production, and thirdly the presence or absence of boundedness of the geographic space. The new model developed in this paper will be referred to as the effective protection model and it will be shown how it is akin in certain respects to the classic Weber model.
Keywords: 330